Kewajiban Negara Indonesia Setelah Meratifikasi International Covenant on Economic Social and Cultural Rights (ICESCR) - Itasari, Endah Rantau (Jurnal Komunikasi Hukum, 2021)
As an ICESCR participating country, Indonesia is bound to implement the provisions of the covenant, especially the use of the institutions in it because Indonesia does not declare a reservation and / or a declaration of the provisions of the Covenant. Five years after Indonesia ratified the covenant, namely in 2010, Indonesia was obliged to send a country report containing the progress of the implementation of the covenant to the Committee on Economic, Social and Cultural Rights. This mechanism is established by the agency / committee concerned to monitor the progress of the implementation of state obligations as stated in the agreement. This is done through various reports that the state must submit within a certain period to the committee concerned. The Committee meets periodically among itself and meetings of delegates of the state parties. During these meetings the committee assessed the report prepared by the state and asked a number of clarifying questions. After that the committee made conclusions and recommendations. Usually the committee identifies positive things that have been achieved, issues that are still crucial and certain recommendations.